Blunt Cerebrovascular Injury Screening Criteria Should Include Motor Vehicle Crash Characteristics. Issue 3 (March 2021) - Farhat-Sabet, Ashley; Lauerman, Margaret; Chavez, Alicia; Lloyd, Joe; Scalea, Thomas; Stein, Deborah
Background: Current screening criteria miss 30% of blunt cerebrovascular injuries (BCVIs). Motor vehicle collisions (MVCs) are the leading BCVI mechanism, and delineating MVC characteristics associated with BCVI formation may augment current screening criteria. Methods: We retrospectively identified BCVI Denver injury screening criteria as able from the Crash Injury Research and Engineering Network (CIREN) database. Severe MVC markers were considered: mean change in velocity (delta-v) greater than 40 km/hour, steering wheel airbag deployment, ejection, or rollover. Results: 93 BCVIs were included. Injury screening criteria were not present in 37/93 (39.8%) BCVIs. Vertebral BCVI more often had injury screening criteria than internal carotid BCVIs (73.2% vs 26.8%, P = .001). There was a significant difference in delta-v (30.78 km/hour vs 51.00 km/hour, P < .001) between BCVI with and without injury screening criteria. BCVI without injury screening criteria more often had safety device use through seatbelt position snug across the hips (94.6% vs 74.5%, P = .01) and pretensioner deployment (92.6% vs 70.2%, P = .04). Examining only drivers, BCVI without injury screening criteria more often had steering wheel airbag deployment (89.7% vs 68.9%, P = .05). Markers of severe MVC were seen in 36/37 (97.3%) BCVIs without injury screening criteria. Discussion: BCVI without injury screening criteria occurred during higher deceleration MVCs with more frequent/appropriate safety device use, suggesting crash deceleration as a mechanism of BCVI formation. Expanding BCVI screening criteria to encompass severe MVCs may lessen the number of BCVI missed.